2007
DOI: 10.1021/pr060668y
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Mueller Glial Cells Trigger the Hallmark Inflammatory Process in Autoimmune Uveitis

Abstract: Spontaneous equine recurrent uveitis (ERU) is an incurable autoimmune disease affecting the eye. Although retinal-autoantigen specific T-helper 1 cells have been demonstrated to trigger disease progression and relapses, the molecular processes leading to retinal degeneration and consequent blindness remain unknown. To elucidate such processes, we studied changes in the total retinal proteome of ERU-diseased horses compared to healthy controls. Severe changes in the retinal proteome were found for several marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 43 publications
4
76
0
2
Order By: Relevance
“…Taken together, we conclude that the presented method is suitable to compare membrane-protein enriched fractions from retinas and results in a much increased analysis depth compared with conventional 2D gel-based proteomics comparisons (5,22).…”
Section: Lc-ms/ms Workflow For Protein Identification From Membrane-ementioning
confidence: 68%
See 1 more Smart Citation
“…Taken together, we conclude that the presented method is suitable to compare membrane-protein enriched fractions from retinas and results in a much increased analysis depth compared with conventional 2D gel-based proteomics comparisons (5,22).…”
Section: Lc-ms/ms Workflow For Protein Identification From Membrane-ementioning
confidence: 68%
“…The spontaneous animal model equine recurrent uveitis (ERU) 1 (3) enabled us to undertake several studies comparing diseased versus healthy condition by proteomic analyses utilizing retina, vitreous and serum samples from horses (4). As a result, we have shown that retinal Mueller cells are players in the pathogenesis of the disease as they transform into a gliotic phenotype-decreasing expression of glutamine synthetase and pigment epitheliumderived factor (PEDF) and simultaneously start expressing interferon gamma (5). This observation is complemented by a quantitative comparison of serum samples with twodimensional-DIGE, where PEDF was also significantly downregulated in ERU cases (6).…”
mentioning
confidence: 99%
“…We reported recently that PEDF is a potent endogenous anti-inflammatory factor (Zhang et al 2006). Decreased intraocular PEDF levels have been observed in patients with diabetic retinopathy and in animal models of type 1 diabetes and spontaneous uveitis (Boehm et al 2003, Zhang et al 2006, Hauck et al 2007. Administration of PEDF into the vitreous significantly inhibits leukostasis and reduces vascular permeability in the retina in STZ-induced diabetic rats, suggesting a potential role of PEDF on leukocyte/ monocyte activation and infiltration in diabetic retinopathy (Yamagishi et al 2006, Zhang et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of ␣A-crystallin during diabetes occurs early in the course of the disease at the same time as vimentin and GFAP, two markers of Mü ller glial cells, the latter indicating an involvement of Mü ller cells in the disease process (39). This finding, correlated with the presence of antibodies against ␣B-crystallins in serum from multiple sclerosis patients and mice with experimental autoimmune encephalomyelitis (40), suggests that the up-regulation of crystallins could be involved in the inflammatory component of diabetic retinopathy.…”
Section: Diabetes Increasesmentioning
confidence: 99%